The New Extensionist: Roles and Cap acities to Strengthen Extension and Advisory Services - Kristen Davis; Rasheed Sulaiman V. (Journal of International Agricultural and Extension Education, 2014)
Extension and advisory services (EAS) perform an important role in agricultural development and help reduce hunger and poverty. Development efforts are increasingly complicated because of challenges such as natural resource depletion and climate change. Agricultural development frameworks have moved from a linear to a more complex systems perspective. Many scholars today use the agricultural innovation systems (AIS) framework as a conceptual model. This framework has three basic elements: all of the actors in the system that brings about agricultural innovation, their interactions, and the institutions and policies governing their interactions. Taking this approach while dealing with the challenges of development today implies new roles and capacities for extension. The authors discuss these new roles and capacities based on an action inquiry process of global dialog and consensus building, to present a vision for EAS within AIS, called the new extensionist(Sulaiman & Davis, 2012). The authors explore individual roles and capacities, and also those at the organizational and system level (Sulaiman & Davis, 2012). The authors discuss the importance of agricultural education in developing these roles and capacities, and bringing more knowledge to bear on the issue
Keywords: Agricultural Innovation System; Capacity-building; Curriculum; Development